2023
DOI: 10.1039/d3sc02549g
|View full text |Cite
|
Sign up to set email alerts
|

Polymer up-cycling by mangana-electrocatalytic C(sp3)–H azidation without directing groups

Abstract: The chemical up-cycling of polymers into value-added materials offers a unique opportunity to place plastic waste in a new value chain towards a circular economy. Herein, we report the selective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Along this line, Ackermann and co-workers developed a mangana-electrocatalyzed C(sp 3 )–H azidation of polymers in the absence of chemical oxidants (Scheme 5). 38 This electrochemical protocol features a wide substrate scope. In addition to polyethylenes, a variety of polypropylenes and polystyrenes are also electrochemically azidated without significant polymer chain degradation.…”
Section: Manganese-catalyzed Electrochemical Transformationsmentioning
confidence: 99%
“…Along this line, Ackermann and co-workers developed a mangana-electrocatalyzed C(sp 3 )–H azidation of polymers in the absence of chemical oxidants (Scheme 5). 38 This electrochemical protocol features a wide substrate scope. In addition to polyethylenes, a variety of polypropylenes and polystyrenes are also electrochemically azidated without significant polymer chain degradation.…”
Section: Manganese-catalyzed Electrochemical Transformationsmentioning
confidence: 99%
“… 96 By applying a low, oscillating cell potential of ±1 V vs. SHE on a Cu electrode, suspended LDPE in an acidic electrolyte containing CuSO 4 was partially electrochemically oxidized, as observed by a significant increase of C O, C–O and C C signals in the post-catalysis IR spectrum of the resulting polymer. 97 However, the approach also led to C sp 3 –C sp 3 bond scission and the formation of smaller molecules such as dodecanoic acid. 96 In another study, Ackermann et al reported the electrochemical azidation of C sp 3 –H bonds in polystyrene ( Fig.…”
Section: Electrochemical Post-polymerization Functionalizationmentioning
confidence: 99%
“…More recently, Román‐Leshkov and co‐workers explored the efficacy of electrochemically formed phthalimido‐ N ‐oxyl (PINO) radicals to activate benzylic C−H bonds in small molecules—reporting a combination of oxidation and C−C bond scission events, with promising initial results applying this strategy toward polystyrene degradation [55] . Earlier this year, Luca and co‐workers reported an electroreductive degradation of poly(ethylene terephthalate), [56] and Ackermann and co‐workers developed a mangana‐electrocatalytic azidation of polystyrene, polyethylene, and polypropylene with up to 7 mol % functionalization [57] . Among these early examples of electrochemical polymer degradation and upcycling, other inspiring work includes that by Stephenson, Stahl, and others to depolymerize lignin using oxidative C−H activation strategies [58–61] …”
Section: Figurementioning
confidence: 99%
“…[55] Earlier this year, Luca and co-workers reported an electroreductive degradation of poly(ethylene terephthalate), [56] and Ackermann and co-workers developed a mangana-electrocatalytic azidation of polystyrene, polyethylene, and polypropylene with up to 7 mol % functionalization. [57] Among these early examples of electrochemical polymer degradation and upcycling, other inspiring work includes that by Stephenson, Stahl, and others to depolymerize lignin using oxidative CÀ H activation strategies. [58][59][60][61] Our group recently reported a strong, biorenewable thermoplastic-poly(2,3-dihydrofuran) (PDHF)-which was synthesized via cationic polymerization of a cyclic vinyl ether.…”
mentioning
confidence: 99%